2021
DOI: 10.3390/agriculture11010079
|View full text |Cite
|
Sign up to set email alerts
|

Grain Yield and Total Protein Content of Organically Grown Oats–Vetch Mixtures Depending on Soil Type and Oats’ Cultivar

Abstract: The yield and quality of crop mixtures depend on natural and agrotechnical factors and their relationships. This research aimed to analyze the grain yield, its components and total protein content of the organically grown oat–vetch mixture on two different soils and depending on the oat cultivar. The three-year field experiment with two crop rotations was carried out. The experiment was set up in the southern Poland on two soils: Stagnic Luvisol (S.L.) and Haplic Cambisol (H.C.). One of four oat cultivars (‘Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
3
5
0
Order By: Relevance
“…During the second cycle, even the first cuts in all harvest management options were made on average 19 d earlier in the monoculture and 35 d earlier in the association than during the first cycle (Table 2). As documented in other research conducted in associated crops (Puzynska et al, 2021) and monocultures (Solomon et al, 2017), it is evident that climatic variations (in temperature and precipitation) between evaluation years affect FY. The productive advantage of the monoculture versus the association is explained by the fact that in the monoculture there were four more cuts in the first cycle and one more cut in the second cycle than in the association.…”
Section: Forage Yieldsupporting
confidence: 64%
“…During the second cycle, even the first cuts in all harvest management options were made on average 19 d earlier in the monoculture and 35 d earlier in the association than during the first cycle (Table 2). As documented in other research conducted in associated crops (Puzynska et al, 2021) and monocultures (Solomon et al, 2017), it is evident that climatic variations (in temperature and precipitation) between evaluation years affect FY. The productive advantage of the monoculture versus the association is explained by the fact that in the monoculture there were four more cuts in the first cycle and one more cut in the second cycle than in the association.…”
Section: Forage Yieldsupporting
confidence: 64%
“…Various species provide complimentary use of environmental resources in a mixture in contrast to pure stands. The recent findings confirmed the benefits of intercropping, such as increased nitrogen uptake by cereals cultivated in a mixture with legumes [1][2][3], and more efficient use of water and nutrients in soil profile [4]. Different species in the mixtures also use field space more effectively [5], i.e., in weather conditions unfavorable for the growth of one species, the companion crop usually grows better [6,7].…”
supporting
confidence: 60%
“…Moreover, none of the species should be too aggressive, especially when mixed with a more valuable protein plant. In the case of well-established mixtures, e.g., oats-common vetch, where cereal component is more competitive toward the legume one, a proper selection of oat cultivars may also significantly affect the quantity and quality of the mixture's yield, i.e., protein content [1]. The oats-common vetch mixtures develop higher LAI and give a higher seed yield in the conventional farming system; however, the share of vetch seeds in the mixtures is higher in the organic system than in the conventional one [2].…”
mentioning
confidence: 99%
“…Only a few studies discuss the influence of oat cultivar selection on the yield of the oat-vetch mixture, e.g., [48]. In our previous studies, we have shown that the oat cultivar is crucial for a good vetch yield, which is also influenced by the type of soil [49]. The share of vetch seeds in the mixture with oats is variable and influenced by several factors [50][51][52].…”
Section: Discussionmentioning
confidence: 99%